An Outlook on Labour Relations in Canada - Carrothers, A. (Relations industrielles / Industrial Relations, 1983)
The object of this paper is to examine the conditions of labour relations in Canada, with a view to trying to assess what is likely to happen in the next few years; and to try to identify what review of policies and practices might be considered in an effort to ameliorate the present unhappy condition of Canadian labour relations.